"t^2\\frac{dy}{dt}+y^2=ty"
"t^2\\frac{dy}{dt}-ty=-y^2"
Dividing equation by "-t^2y^2" :
"-y^{-2}y'+y^{-1}t^{-1}=t^{-2}"
Substituting "z=y^{1-2}=y^{-1}" , "\\frac{dz}{dt}=z'=-y^{-2}y'" , therefore: (1)
"z'+\\frac z t =\\frac 1 {t^2}"
Substituting "z=uv" , "z'=u'v+uv'" : (2)
"u'v+uv'+\\frac {uv} t = \\frac 1 {t^2}"
"u'v+u(v'+\\frac {v} t) = \\frac 1 {t^2}" (3)
Setting the part inside () to 0 and separating variables:
"v'+\\frac {v} t=0"
"\\frac {dv}{dt}=-\\frac v t"
"\\int \\frac {dv} v = - \\int \\frac {dt} t"
"ln(v) = -ln(t)+ln(k)"
"v=\\frac k t" (4)
Putting "v" from (4) into equation (3):
"u'\\frac k t = \\frac 1 {t^2}"
"\\int kdu = \\int \\frac {dt}t"
"u= \\frac 1 k (ln(t)+C)"
Finding z from (2):
"z=uv=\\frac 1k (ln(t)+C)\\frac kt = \\frac{ln(t)+C}{t}"
Finding y from (1):
"y=z^{-1}=\\frac t {ln(t)+C}"
Answer: "y=\\frac t {ln(t)+C}"
Comments
Leave a comment